2009
DOI: 10.1111/j.1574-695x.2009.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic healthy slaughterhouse workers in South Korea carrying Shiga toxin-producingEscherichia coli

Abstract: A total of 1602 stool samples from healthy employees in a slaughter company were screened by PCR for Shiga toxin (Stx)-producing Escherichia coli (STEC). The PCR product of Stx-encoding genes was detected in 90 (5.6%) of 1602 stool samples. Among the 90 stx-positive workers, the Residual Products Handlers and Slaughterers had rates of 8.0% and 6.0% -higher than Inspectors, Grading Testers and Livestock Hygiene Controllers at 3.3%, 2.0% and 3.5%, respectively. Forty-nine (54.4%) were shown to have stx2; 25 (27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Our findings are in line with previous studies reporting the spread of STEC in healthy individuals (28)(29)(30) and the occurrence of stx genes in stool samples in the general population (31). In two of those studies (29,31), stx-positive results were obtained in a first screening by PCR.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are in line with previous studies reporting the spread of STEC in healthy individuals (28)(29)(30) and the occurrence of stx genes in stool samples in the general population (31). In two of those studies (29,31), stx-positive results were obtained in a first screening by PCR.…”
Section: Discussionsupporting
confidence: 82%
“…In two of those studies (29,31), stx-positive results were obtained in a first screening by PCR. Considering the methods described in those reports, it cannot be excluded that those authors detected Stx phages in addition to the STEC strains isolated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that humans can act as healthy asymptomatic carriers of non-O157 STEC (30). In addition to humans, rabbits also harbored STEC carrying both stx 1 and stx 2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…National studies in Korea showed that enterohemorrhagic E. coli (EHEC) is present in workers in the farm industry as well as slaughter houses, especially among people who have more opportunities to come into contact with cattle [14,15]. Therefore, not only carcasses during slaughter but also cattle on farms during the pre-slaughter stage should be treated to prevent the spread of STEC.…”
Section: Introductionmentioning
confidence: 99%